Daily change patterns in mindfulness and psychological health: A pilot intervention. Issue 3 (29th August 2020) - Kim, Shin Ye; Suh, Hanna; Oh, Wonjung; Daheim, Jacob
Abstract: Objective: This study examined the differences in first‐year college students' daily change trajectories in subjective happiness, depression, anxiety, stress, and state mindfulness. Method: A 5‐day, online mindfulness‐based intervention (MI) condition and stress management (SM) condition were employed in 247 first‐year college students. Results: Students in both the MI and SM conditions displayed similar significant linear declines in anxiety and stress, but there were significant differences between the two conditions, including: (1) the MI condition showing a significant linear increase in subjective happiness compared with no change in the SM condition and (2) the SM condition showed a significant linear decrease in depression compared to no significant change in the MI condition. Conclusion: Brief online interventions—whether MI or SM—can promote better mental health and reduce psychological distress. The results also lend support for MI's differential influence on first‐year college students' happiness and SM's differential influence on their depression.